Performance of Composite Filters Assembled from Multiple Layers of Basic Filtration Media - Peng Wang; Zhen Liu; Da-Ren Chen (Aerosol and Air Quality Research)
Abstract There is a severe shortage of face masks and N95 respirators due to the current COVID-19 pandemic, particularly in countries that were not well prepared in advance. In order to help ease the supply demands of these resources, a strategy of using multiple layers of basic filtration media to construct a composite filter that can match the particle collection efficiency offered by a N95 filtering facepiece respirator (FFR) is proposed. In this study, the filtration performances of four face masks and one N95 respirator using the same test protocol (as a reference) were first compared. Composite filter samples composed of multiple layers of basic face mask and MERV13 furnace media were then constructed and the filter performance of the composite filters was investigated. As expected, the minimum particle collection efficiency of the N95 respirator media sample was higher than 95% and the efficiency of the samples from the four tested face masks varied from 71.8% to 83.6%. The Figure of Merit (FOM) values of the face mask samples were generally half that of the N95 media sample. It was found that a N95-comparable collection efficiency can be achieved by combining two/three layers of face mask media but at the expense of a higher media pressure drop. Additionally, the composite filter samples made up of three/five layers of MERV13 furnace media could approach the FOM offered by the N95 media without the increased pressure drop. It was also found that the measured collection efficiency of multiple-layered filter media was not equal to the calculated in the test particle size range. Further studies are required to identify the reason(s).